Uso de Tecnologias Digitais da Informação e Comunicação em um Curso de Inglês para Fins Específicos na Área Jurídica - Rossini, Adriana Marroni Zaniol Palombo (2016)
This study aims at investigating how the use of digital information and communication technologies (TDIC) can help the development of reading comprehension on a course of English for Specific Purposes addressed to legal practitioners. The theoretical framework includes the concepts of English for Specific Purposes as Hutchinson and Waters (1987), Dudley-Evans and St. John (1998), Ramos (2004, 2009), Basturkmen (2010), Paltridge (2014), Johns (2015 ); the use of technological resources in teaching and learning languages in the area of Computer-Assisted Language Learning (CALL), according Chapelle (2010); Leffa (2006); Hubbard (2012) and the Pedagogical Ramos Proposal (2004) for the application of gender in language teaching that based the design of the activities supported by TDIC and analyzed in this research. Methodologically, this research is characterized as a case study (Stake, 1998; Johnson, 1992; Yin, 2010) and made use of the following instruments for data collection: questionnaires at three moments of the course – at the beginning, to raise and describe the profile of students, during the course, to identify the students’ perceptions about the use of digital technologies to assist in reading; and in the end to learn about the students’ perceptions as to their progress in the development of reading comprehension and vocabulary acquisition. Interviews were also held after the completion of the activities with digital resources and field notes were taken. The results revealed that, although little known online concordancers aroused interest and even facing difficulties students managed to use them. However, according to the participants’ perception online dictionaries were more effective in helping the understanding of legal texts written in English. However, it was revealed that students underuse this digital resource and the activities implemented during the course enabled the familiarization and greater knowledge of these resources. This study showed that digital resources, especially online dictionaries, helped expand both the knowledge of the legal language in English and knowledge of the English language in general. Resources potentiated the knowledge and independence offered to students in order to enable them to solve their difficulties in reading and vocabulary. This research aims to contribute to the English for Specific Purposes area, mainly with respect to legal English area and aims to bring contributions to the research on digital technologies applied to the development of understanding written texts in English